Answers

2015-04-24T16:50:55+05:30
If a+b+c=0
then a+b=-c
now cube both  the sides i.e LHS n RHS                   
(a+b)^3=(-c)^3                                                         (a+b)^3 = a^3+b^3+3ab(a+b)
a^3+b^3+3ab(a+b)=-c^3                           
now transpose -c^3 to LHS
a^3+b^3+c^3+3ab(a+b)=0
a^3+b^3+c^3+3ab(-c)=0 [reason: a+b = -c ]
a^3+b^3+c^3-3abc=0
now  transpose -3abc to RHS
a^3+b^3+c^3=3abc

Thus proved a^3+b^3+c^3+3ab




2 4 2
Mark it as the best plz........ Plz
2015-04-24T20:29:09+05:30
By the formula,
a^3+b^3+c^3-3abc=(a+b+c)(a^2+b^2+c^2-ab-bc-ac)
                           =0*(a^2+b^2+c^2-ab+bc+ac)
                           =0
:. a^3+b^3+c^3=3abc
0